Feasibility Analysis of Business Processing of Clove Leaf Waste Into Clove Leaf Oil in Lede District, Taliabu Island - Salimu, Salman; Rianda, La; Alwi, La Ode (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2023)
This study aimed to analyze the feasibility of processing clove leaf waste into clove leaf oil in Lede District, Taliabu Island Regency. The analysis in this study uses financial feasibility analysis. The results showed that clove leaves contain antibacterial compounds such as flavonoids, phenolics, triterpenoids, tannins, phenolics, eucalyptol, α-cardinal, caryophyllene, and limonene. Dried fallen leaves are the primary raw material used to produce clove leaf oil. The results showed that the analysis of the financial feasibility aspect of clove leaf oil refining carried out in Balohang Village, Lede District, Taliabu Island Regency, was declared feasible for development with a positive NPV feasibility value of 1,345,940,035 for five years of operation, an IRR of 169.93%, a Net B/C of 1.2, a PBP = 0.58, an ROI of 88%, and production of BEP 685.45 at a BEP price of IDR 106,4455. Based on the analysis of non-financial descriptive aspects, namely the estimation of market and technical aspects, the clove leaf oil refining business in Balohang Village has adequate opportunities to run.